Analyzing Madinah Arabic: A Web-Based Arabic Language Learning Tool - Sinaga, Mailani (Kitaba, 2023)
The advancement of technology has become increasingly sophisticated from era to era, permeating various fields, including education. Education must also adapt to the changing times. Therefore, instructional methods must be designed to follow the current trends. By harnessing technology, learning can easily take place anywhere and anytime. There are numerous platforms that can be utilized for learning, particularly in the Arabic language. One such platform is Madinah Arabic, which is web-based. The aim of this research is to explore Madinah Arabic from several aspects, with the outcomes of this study serving as a foundation for further development. This research employs a qualitative descriptive method through a literature study, involving the collection of information and scholarly works related to a literature review of academic sources. Primary sources are derived from the Madinah Arabic website, while secondary sources consist of relevant journal articles. The resulting discussions reveal that Madinah Arabic is a website for Arabic language learners, characterized by a simple design, a division of materials into premium and free content, as well as a presentation of materials in various formats (videos, audios, audio-visuals, texts, images). Moreover, the website also offers lessons for non-Muslims who solely wish to learn the language. The materials are also presented through interaction via YouTube by native speakers, enabling learners to become more acquainted with proper pronunciation and enhancing their listening skills